Advances in prescription drug monitoring program research: a literature synthesis (June 2018 to December 2019). Issue 4 (July 2020) - Delcher, Chris; Pauly, Nathan; Moyo, Patience
Abstract : Purpose of review: Nearly every U.S. state operates a prescription drug monitoring program (PDMP) to monitor dispensing of controlled substances. These programs are often considered key policy levers in the ongoing polydrug epidemic. Recent years have seen rapid growth of peer-reviewed literature examining PDMP consultation and the impacts of these programs on diverse patient populations and health outcomes. This literature synthesis presents a review of studies published from June 2018 to December 2019 and provides relevant updates from the perspective of three researchers in this field. Recent findings: The analyzed studies were primarily distributed across three overarching research focus areas: outcome evaluations ( n  = 29 studies), user surveys ( n  = 23), and surveillance ( n  = 22). Identified themes included growing awareness of the unintended consequences of PDMPs on access to opioids, effects on benzodiazepines and stimulant prescribing, challenges with workflow integration across multiple specialties, and new opportunities for applied data science. Summary: There is a critical gap in existing PDMP literature assessing how these programs have impacted psychiatrists, their prescribing behaviors, and their patients. Although PDMPs have improved population-level monitoring of controlled substances from medical sources, their role in responding to a drug epidemic shifting to illicitly manufactured drugs is under scrutiny.